2010
DOI: 10.1515/cclm.2011.092
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturization and globalization of clinical laboratory activities

Abstract: Clinical laboratories provide an invaluable service to millions of people around the world in the form of quality diagnostic care. Within the clinical laboratory industry the impetus for change has come from technological development (miniaturization, nanotechnology, and their collective effect on point-of-care testing; POCT) and the increasingly global nature of laboratory services. Potential technological gains in POCT include: the development of bio-sensors, microarrays, genetics and proteomics testing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Others reported that US centers invested in satellite clinics abroad for the supply of transport PGD . With transport PGD, CBRS enter the globalization of laboratory practices and participate in the intensification of the international circulation of human biological samples .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others reported that US centers invested in satellite clinics abroad for the supply of transport PGD . With transport PGD, CBRS enter the globalization of laboratory practices and participate in the intensification of the international circulation of human biological samples .…”
Section: Resultsmentioning
confidence: 99%
“…A test may be more attractive abroad because of its lower price . Large test volumes, new molecular diagnosis approaches combined with effective automation and a network of distant satellite clinics may produce important savings and lower the price in certain centers . For many clinics, resorting to transport PGD can be more economically attractive than investing in the development of a local PGD unit .…”
Section: Resultsmentioning
confidence: 99%
“…With increasing miniaturization trends from the micro-to the nanoscale regime in biodetection technology (8385), future applications of ZnO NRs may accordingly favor the use of single, rather than ensembles of, ZnO NRs as distinct detection elements, especially for in vivo imaging and in vitro assays requiring extremely low-volume and high-throughput analyses. Therefore, the previous studies discretely probing individual ZnO NRs may provide a basis for both the design of an optimized detection platform with large signal enhancement and accurate signal interpretation of fluorescence-based bioassays.…”
Section: Biomedically Relevant Optical Properties Of Zno Nanorodsmentioning
confidence: 99%
“…One may raise the point that from the perspective of a developing country, personalized applications might not be economically viable also because prevalent disease pattern differs. However, it is worth to note that the same devices and supportive infrastructure can be tweaked for both clinical and laboratory diagnosis at the health facility level [16]. Indeed, an initiative that is working to address this already exists—the MoDiSe [17].…”
Section: Introductionmentioning
confidence: 99%